Carpal laxity syndrome in forty-three puppies - Çetinkaya, M. A.; Yardimci, C.; Sağlam, M. (Veterinary and Comparative Orthopaedics and Traumatology, 2007)
Forty-three dogs with carpal laxity syndrome were included in the study. The cases were assessed with clinical and radiographical examinations. The case histories were obtained from patient owners. We recommended exercise and commercially available balanced diets for the treatment. In all cases, the clinical recovery period varied between one to four weeks. Healing occured by the second week in the majority of cases (65.11%). The deformity was observed more frequently in male dogs (n=30) than in female dogs (n=13), and in six- to eight-week-old dogs.Carpal Laxity Syndrome is a more general term, used for both hyperextension and hyperflexion deformity. Malnutrition or over-nutrition of rapidly growing large breed puppies causes weakness and irregular tension between extensor and flexor muscle groups, which leads to laxity of the carpal joint. Exercise and commercially available balanced diets without any other treatment is usually enough to achieve physical and functional recovery.
Keywords: Carpal laxity; carpal extensor deformity; carpal flexor deformity; puppy